Serious Game Technology to Strengthen National Defense Insights for Marginalized Children of Indonesian Immigrant Workers: Serious Game Technology untuk Penguatan Wawasan Bela Negara bagi Marginalized Children Pekerja Imigran Indonesia - Alfyananda Kurnia Putra; Arif Ahmad Widianto; Syamsul Bachri; Tasya Khairunisa; Q. Vanti Dian; Kristanti; Diky Al Khalidy (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
The actualization of state defense is a means of socializing and internalizing the noble values of the Indonesian nation. However, this process is an obstacle for children of Indonesian Migrant Workers (PMI) who were born and raised in Malaysia without official documents (illegal), so access to state defense education and local wisdom is very limited. Problems such as low knowledge about awareness of national defense attitudes and a lack of national spirit will emerge. Further problems will arise, feelings of injustice will arise, giving rise to threats to physical, ideological and political, economic, cultural and protection issues. The solution to the partners' problems, namely PMI children at the Johor Bahru Indonesian School (SIJB), is the development of serious game-based learning media about defending the country and local wisdom. The development stages start from analysis, design, and development. The product results will be given to partners as a medium to prepare the spirit of PMI children before they are drawn back to Indonesia. The result of this community service activity is the role playing game serious game product Nusantara Quest: Jiwa Garuda Saga. With this community service activity, the partner party, namely SIJB, can have adequate media to convey state defense material and local wisdom to students continuously.